Emotions and Teachers’ Professional Identity: Relations and Incidence (2017)
Teachers’ Professional Identity (TPI) is closely and continuously linked to emotions from the very first moment when identity profile is structured and in every single transformation suffered. Studies that address identity are now more focused on gaining new perspectives on when, where and how to be rather than raising questions about who you are. In this context, this article presents results concerning the aspects related to the identity and the feelings of seventeen last semester students from the Universidad Pedagógica y Tecnológica de Colombia towards the profession they have chosen. The research used the case study with multiple units of analysis and the indepth interview as data collection methods, which were analyzed thanks to the computer program ATLAS TI. In conclusion, the identities are diverse, dynamic, and complex and they are built from intrapersonal components, emotional experiences and experiences in classroom practice, in accordance with the characteristics of the environment.